Human Umbilical Cord Mesenchymal Stem Cell-Derived Exosomes Improve Ovarian Function and Proliferation of Premature Ovarian Insufficiency by Regulating the Hippo Signaling Pathway - Li, Zhongkang; Zhang, Mingle; Zheng, Jiahua; Tian, Yanpeng; Zhang, Huihui; Tan, Yi; Li, Qian; Zhang, Jingkun; Huang, Xianghua (Frontiers in Endocrinology, 2021)
Background Premature ovarian insufficiency (POI) is associated with severe physical damage and psychological burden on women. Transplantation of exosomes is an encouraging regenerative medicine method, which has the potential for restoring ovarian functions on POI with high efficiency. This study aims at evaluating the therapeutic efficacy of human umbilical cord mesenchymal stem cell-derived exosomes (hUCMSC-Exos) on ovarian dysfunction of POI and the role of Hippo pathway in this exosome-mediated treatment. Methods POI mice models were established through intraperitoneal injection of cyclophosphamide. Subsequently, transplantation of hUCMSC-Exos was conducted to administer POI mice. Ovaries and plasma of these mice models were harvested after two weeks of treatment. Ovarian morphology and follicle number were assessed by hematoxylin and eosin staining. Moreover, ELISA was used to detect hormone levels, which are related to ovarian function in serum. To assess the recovery of reproductive ability, we recorded the rate of pregnancy, the amount of offspring, and the time of birth in different groups. To explore the underlying mechanisms of exosome-mediated treatment for ovarian function recovery, the proliferation of ovarian cells in vivo was detected by immunohistochemistry and immunofluorescence staining. Additionally, we conducted EdU and CCK-8 assays to assess the proliferative ability of ovarian granulosa cells (GCs) that were cultured in vitro. Western blot analysis was conducted to estimate the proteins levels of Hippo- and proliferation-associated molecules in vivo and in vitro. Results After transplantation of hUCMSC-Exos, the ovarian function-related hormone levels and the number of ovarian follicles returned to nearly normal degrees. Meanwhile, there was a significant improvement in reproductive outcomes after exosomal treatment. Furthermore, the improvement of ovarian function and proliferation was associated with the regulation of Hippo pathway. In vitro, co-culture with exosomes significantly elevated the proliferation of ovarian GCs by regulating Hippo pathway. However, the positive effects on the proliferation of GCs were significantly depressed when key Hippo pathway molecule was inhibited. Conclusion This study suggested that hUCMSC-Exos promoted ovarian functions and proliferation by regulating the Hippo pathway. Therefore, exosomal transplantation could be a promising and efficient clinical therapy for POI in the near future.